The rule of meeting for Friday Lesson between following and fabrication "Jurisprudence fundamentalism study" - Al- Manasyeh, Mohammad Amin (Journal of Islamic Sciences, 2021)
This research aims to indicate the ruling of the meeting for the study before Friday according to an authentic methodology based on modern, fundamentalist, doctrinal and purpose aspects. The study adopted a complex approach of descriptive and analytical approaches based on extrapolation and comparison, taking into account the steps and conditions of scientific research used in Islamic studies. After examining the merits of the meeting to examine Friday between the followers and the innovation of evidence and objections, it was found that it was permissible to say that it was permissible, both in terms of the validity and preponderance of the evidentiary orientation, in terms of the strength and implications of the evidence and its implications for the purpose, and documents that emerged through a set of evidence; fundamentalism and jurisprudence.